Answer:
Explanation:
The given system of equations is expressed as
y = 3x - - - - - - - - - - - - -1
2y = 6x - - - - - - - - - - - - -2
Dividing the left hand side and the right hand side of equation 2 by 2, it becomes
y = 3x - - - - - - - - - - - - -3
Subtracting equation 3 from equation 1, it becomes
0 = 0
The system of equations has infinitely many solutions because whatever values of x and y that would satisfy the first equation would also satisfy the second equation.
Your answer is right because you substituted equation 1 into equation 2.